PENYUSUNAN LAPORAN KEUANGAN SESUAI SAK EMKM DAN ANALISA COMMON SIZE UNTUK MENILAI KINERJA KEUANGAN MONA HIJAB FASHION - Putria; Sjamsul Hidayat; Andrianto (Majalah Ekonomi, 2021)
The purpose of this research is to provide a comprehensive understanding and preparation of financial records so as to produce accountable financial reports for use by interested parties. This research is a qualitative descriptive study. Data collection techniques used by interviews, observation and documentation. The data used are primary data and secondary data. The results of the study produce reports in accordance with SAK EMKM which consists of income statements, statements of financial position and notes to financial statements. From the preparation of the financial statements, Mona Hijab Fashion in 2019 experienced a loss, this is because there is no preparation of financial reports according to EMKM standards so this also affects the analysis of financial performance in the business.